STUDY THE EFFECT CHANGE IN DS OF A DX-EVAPORATOR AIR CONDITIONING SYSTEM USING MANUAL CONTROL - Amani D. Salman; Alaa R. Al-Badri; Ahmed H. Al-Hassani (European Journal of Research Development and Sustainability, 2023)
Air conditioning systems consume high rates of energy, with the compressor consuming the largest portion of this energy. In this study, the performance of a variable-speed air conditioning system with a capacity of one ton was tested, which contains a compressor, a variable-speed supply fan, an electronic expansion valve, and a DX evaporator with R-410A refrigerant. The results showed that increasing DS does not affect the performance coefficient at a fixed compressor speed. Moreover, when the compressor speed increases, the performance factor decreases from 4.2 to 3.5 due to increased energy consumption.